LEGAL STUDY ON ETHICAL ISSUES IN THE USE OF ARTIFICIAL INTELLIGENCE FOR LEGAL DECISIONS: CRITICAL LITERATURE REVIEW - Hanafi, Imam; Syah, Kaharuddin; Judijanto, Loso; Rachmawati Maruf, Irma; Subihat, Ihat (Faculty of Law, Universitas Pekalongan, 2024)
This comprehensive research embarks on meticulously exploring the intricate ethical nuances at the convergence of artificial intelligence (AI) and legal decision-making. Through an exhaustive literature review, the study meticulously navigates the complexities woven into algorithmic bias, the multifaceted dimensions of data privacy concerns, the profound implications on human agency, imperatives surrounding transparency, the socio-economic impacts stemming from the integration of AI, and the global perspectives that cast a profound influence on this intricate landscape. The synthesis of these insights reveals a dynamic interplay between the rapid evolution of technological capabilities and the intricate ethical considerations that underpin responsible AI integration into legal frameworks. The study underscores the need for ongoing interdisciplinary discourse, urging scholars, practitioners, and policymakers to engage in a continuous dialogue to ensure that ethical frameworks evolve in tandem with the relentless progression of AI technology. The conclusion advocates for a flexible and adaptive ethical framework poised to navigate the evolving ethical horizon, thereby ensuring AI's judicious and equitable integration into legal decision-making.